Paradoxical Philogyny: The Comtesse de Murat’s Defense of Women and Female Friendship in Dialogue with François Poullain de la Barre and Gabrielle Suchon - Denzel, Valentina (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2023)
In her memoirs, the Comtesse de Murat replies to the long list of misogynist accusations made in Abbé de Villiers’s Mémoires de la vie du comte D*** avant sa retraite (1696) by criticizing gender inequalities and by emphasizing female virtue. This article focuses on Murat’s positive representation of female friendship, whereby she denounces Villiers’s allegation that women’s affection is guided by greed. While Murat’s protagonist proves the contrary through her devoted comradeship with Mademoiselle Laval, not all female relationships in Murat’s memoirs are portrayed in a favourable light. The protagonist’s femme de chambre, for example, confirms Villiers’s critique of female covetousness and disloyalty. Even the relationship between the protagonist and Mademoiselle Laval is tarnished by sapphic allusions that are, however, outwardly denied. This article analyzes Murat’s paradoxical representation of women that builds on pro-feminist arguments by François Poullain de la Barre and Gabrielle Suchon. Yet, this paradox is lessened in Murat through the attribution of immoral acts to both sexes. Furthermore, the intimate connection between Mademoiselle Laval and the protagonist lends itself to a double entendre that advocates for homoeroticism and a preference for female-centred communities over heterosexual relationships.